2005
DOI: 10.1016/j.nimb.2005.03.155
|View full text |Cite
|
Sign up to set email alerts
|

Natural widths of hypersatellite K-X-ray lines and lifetimes of double K-hole states in mid-Z atoms

Abstract: K-X-ray spectra of Zr, Nb, Mo and Pd targets bombarded with 250 MeV carbon and 360 MeV oxygen ions are studied with high resolution diffraction spectrometry. Relative yields and natural widths of the K h a 1,2 hypersatellite lines are determined and compared with those of the diagram lines. The widths of K h a 1,2 lines are compared with the new phenomenological formula which takes into account the retardation of the K h a 1 transition in the LS coupling scheme. The data significantly exceed the expected value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…However, it was found that the experimental natural widths of the K h α 1 and K h α 2 lines significantly exceed the values obtained from the formula proposed by Rzadkiewicz et al [2], but are in good agreement with the simple statistical formula. Moreover, the experimental lifetimes of the double K -hole states (deduced from their measured natural widths) are close to those predicted by the statistical formula, but significantly shorter than the values determined by means of the formula proposed by Rzadkiewicz et al [2].…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…However, it was found that the experimental natural widths of the K h α 1 and K h α 2 lines significantly exceed the values obtained from the formula proposed by Rzadkiewicz et al [2], but are in good agreement with the simple statistical formula. Moreover, the experimental lifetimes of the double K -hole states (deduced from their measured natural widths) are close to those predicted by the statistical formula, but significantly shorter than the values determined by means of the formula proposed by Rzadkiewicz et al [2].…”
Section: Introductionsupporting
confidence: 60%
“…In a work by Rzadkiewicz et al [2], the experimental widths of K h α 1,2 lines have been compared with two formulae: the first one-statistical (proposed by Mossé et al [7])-is based on the assumption K K ≈ 2 K and the second one (phenomenological-proposed in [2]) takes into account the possibility of enlarging the lifetime of the K −2 hole state (and correspondingly decreasing the natural width of the hypersatellite line) as a result of closing the K h α 1 de-excitation channel in the pure LS coupling scheme. However, it was found that the experimental natural widths of the K h α 1 and K h α 2 lines significantly exceed the values obtained from the formula proposed by Rzadkiewicz et al [2], but are in good agreement with the simple statistical formula.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiative transition probabilities were predicted by Campbell and Wang [15] and Perkins et al [16] for all elements and transitions, but experimental determinations are unusual, although they are crucial to validate the assumptions involved in the numerical assessments based on theoretical models, such as multiconfigurational Dirac-Hartree-Fock atomic-structure calculations [17]. Different approaches have been introduced in this kind of calculations to account for 3d K hypersatellite emissions [3,18,19], with uneven comparisons with experimental values [20]. Finally, some effort has been devoted to characterize the structures related with the radiative Auger effect (RAE) associated to K shells [21,22], a phenomenon which has recently drawn the attention for the case of isolated quantum structures [23,24].…”
Section: Introductionmentioning
confidence: 99%